2017
DOI: 10.1259/dmfr.20160107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vertical root fractures in intact and endodontically treated premolar teeth by designing a probabilistic neural network: an ex vivo study

Abstract: Objectives: Detection of vertical root fractures (VRFs) in their initial stages is a crucial issue, which prevents the propagation of injury to the adjacent supporting structures. Designing a suitable neural network-based model could be a useful method to diagnose the VRFs. The aim of this study was to design a probabilistic neural network (PNN) to diagnose the VRFs in intact and endodontically treated teeth of periapical and CBCT radiographs. Also, we have compared the efficacy of these two imaging techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 19 publications
1
71
0
8
Order By: Relevance
“…A CNN trained on a limited amount of image segments showed discrimination ability similar to that of live dentists assessing periodontal bone loss with panoramic radiographs (Krois et al ). Johari et al () modelled a probabilistic neural network (PNN) to detect vertical root fractures in vital and endodontically treated teeth using periapical and CBCT radiographs. They confirmed that the neural network diagnosed fractures more effectively using CBCT images than periapical radiographs, suggesting that this model may benefit endodontic assessments (Johari et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CNN trained on a limited amount of image segments showed discrimination ability similar to that of live dentists assessing periodontal bone loss with panoramic radiographs (Krois et al ). Johari et al () modelled a probabilistic neural network (PNN) to detect vertical root fractures in vital and endodontically treated teeth using periapical and CBCT radiographs. They confirmed that the neural network diagnosed fractures more effectively using CBCT images than periapical radiographs, suggesting that this model may benefit endodontic assessments (Johari et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Johari et al () modelled a probabilistic neural network (PNN) to detect vertical root fractures in vital and endodontically treated teeth using periapical and CBCT radiographs. They confirmed that the neural network diagnosed fractures more effectively using CBCT images than periapical radiographs, suggesting that this model may benefit endodontic assessments (Johari et al ). Kositbowornchai et al () also created a neural network to diagnose vertical root fractures using intraoral digital radiographs and evaluated the diagnostic performance of their neural network.…”
Section: Discussionmentioning
confidence: 99%
“…The possible and future clinical applications of artificial intelligence and neural networks is the prediction of a phenomenon. Probabilistic neural networks can be used in dentistry to predict fractures, as Johari et al indicated, where a probabilistic neural network was designed to diagnose a fracture in endodontically treated teeth [48].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, automatic methods based on deep neural networks have been tested for several purposes, which are as follows: classification, image registration, segmentation, lesion detection, image retrieval, image guided therapy, image generation, and enhancement . Most recently, radiomics and AI research have been advancing in the dental field, revealing the potential of these technologies to substantially improve clinical care …”
Section: Radiomics and DL Applications In Radiologymentioning
confidence: 99%